Perception of Pay Satisfaction on Employee Work Attitude and Behavior in Pakistani E-Commerce Companies - Muhammad Sufyan; Yasmine Nasution (Indonesian Interdisciplinary Journal of Sharia Economics, 2024)
The e-commerce sector in Pakistan has experienced significant growth over the past decade, with major platforms like Daraz OLX and others driving economic development and job creation. This growth, however, brings challenges in human resource management, particularly concerning employee compensation. This study investigates the perception of pay satisfaction on employee work attitude and behavior in Pakistani e-commerce organizations. A quantitative cross-sectional survey was employed, targeting 240 employees in Pakistan. Data were collected and analyzed using descriptive statistics and Structural Equation Modeling (SEM), the results reveal that pay satisfaction significantly and positively influences job satisfaction, organizational commitment, and employee productivity, respectively. Satisfied employees are more likely to be committed, satisfied, and productive. Enhancing pay satisfaction can foster a more effective workforce, making a strong case for integrating pay satisfaction strategies into organizational policies to improve performance and employee well-being. This underscores the importance of regularly evaluating and adjusting pay strategies to align with employee expectations and market standards, thereby enhancing overall organizational effectiveness.